Effects of glyphosate and polyoxyethylene amine on metabolic rate and energy reserves of Procambarus clarkii juveniles - Frontera, Jimena Laura (2014)
P. clarkii juvenile crayfish were exposed during 60 days to sublethal concentrations of glyphosate (G), polyoxyehtylene amine (P) or a combination of both (G+P), together with a control group of aged tap water (C). At the end of the experiment, the following statistical differences were noted, with respect to control: 1) a lower metabolic rate in both G and G+P groups, 2) a higher glycemia in G group with no differences in hemolymphatic lactate levels, 3) a lower muscle glycogen levels in both P and G+P groups, 4) a lower level of protein muscle in the P group. Taken together, these results suggest that glyphosate may cause a metabolic arrest. Additionally, under chronic exposure conditions, polyoxyehtylene amine acts as a strong stressor, leading to the utilization of both muscle carbohydrate and protein reserves.